PERBEDAAN HASIL BELAJAR MATA KULIAH GELOMBANG MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF BERBASIS INQUIRI MAHASISWA PENDIDIKAN FISIKA. - Syifa’ul Gummah; Sukainil Ahzan (Universitas Pendidikan Mandalika, 2014)
This study aims to determine the difference in learning outcomes of 'Wave courses' between groups of students using cooperative learning models based on inquiry and conventional methods. The sample of this research is Student of Physics Education Department in FPMIPA IKIP Mataram class A and B determined by random sampling technique. Data retrieval was performed with tests for cognitive learning outcomes. Research data were taken through pre-test and post-test scores. The research hypothesis was tested by using t test statistic. The results showed that there were differences in students' cognitive learning outcomes between groups of cooperative learning models based on inquiry with conventional learning model expressed by t-test (2.36)> t-table (1.96) at 5% significance level.